Absence of Correlation between X Chromosome Inactivation Pattern and Plasma Concentration of Factor VIII and Factor IX in Carriers of Haemophilia A and B - Ørstavik, Karen Helene; Scheibel, Elma; Ingerslev, Jørgen; Schwartz, Marianne (Thrombosis and Haemostasis, 2000)
Haemophilia A and B are X-linked disorders which are due to a reduced activity of coagulation factor VIII or IX, respectively. Female carriers have a wide range of plasma concentration of factor VIII or factor IX, and may in rare cases have an affected phenotype. In order to investigate if this variation is related to X chromosome inactivation, we determined the X inactivation pattern in 31 haemophilia A and 15 haemophilia B carriers, using a PCR in the androgen receptor locus in blood DNA. Seven of the haemophilia A carriers and none of the haemophilia B carriers had a skewed pattern (≥80:20). One of the skewed haemophilia A carriers had a low plasma concentration of factor VIII (0.15 U/ml), but the remaining 6 carriers did not differ in factor VIII concentration from that of carriers with a random X inactivation pattern. One carrier with a high factor VIII concentration (2.0 U/ml) did not have a skewed pattern. Similarly, for the haemophilia B carriers, there was no tendency to a more skewed X inactivation pattern in the carriers with low or high factor IX concentrations. In addition, we analysed a female with haemophilia B who was heterozygous for the mutation R180W in the factor IX gene. She had a random X chromosome inactivation pattern. We conclude that the wide range in plasma concentration of factor VIII and factor IX in haemophilia A and B carriers cannot in general be explained by the X chromosome inactivation pattern in peripheral blood cells.
Keywords: Haemophilia; X chromosome inactivation; carrier; female